2018
DOI: 10.21037/jtd.2018.06.86
|View full text |Cite
|
Sign up to set email alerts
|

Benchmark values for transthoracic esophagectomy are not set as the defined °∞best possible°±°™a validation study

Abstract: Benchmark values assessing postoperative morbidity after MIE do not represent the defined "best achievable" results after completed learning curves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Strengths of our study are completed learning curves, shown to affect outcomes [2224], and excellent and stable reported results [13]. Therefore, technical difficulties or variations in the operations are minimal, and differences between groups in outcomes can be assumed to be mainly due to patient-specific factors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Strengths of our study are completed learning curves, shown to affect outcomes [2224], and excellent and stable reported results [13]. Therefore, technical difficulties or variations in the operations are minimal, and differences between groups in outcomes can be assumed to be mainly due to patient-specific factors.…”
Section: Discussionmentioning
confidence: 99%
“…All patients underwent en bloc lymphadenectomy with 3-dimensional optics used since June 2013. Perioperative standardized treatment protocol, extent of lymphadenectomy, and follow-up have been previously described [13, 15]. The median follow-up time was 21 (IQR 11-38) months.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Positive resection margin, the number of examined lymph nodes and readmission rate were reported as in a previous study (22). R0 resection was defined as complete resection with at least 1 mm resection margin.…”
Section: Patientsmentioning
confidence: 99%